(untitled) (Future Cities and Environment, 2024)
In achieving SDG-11 Sustainable Smart City, many government strategies and initiatives need to be implemented, especially involving transportation. In Malaysia, transportation is a medium that connects job opportunities with people’s welfare. Nonetheless, Malaysia still has no restrictions on vehicle ownership, especially in urban areas like Kuala Lumpur. This study was carried out to achieve the following objectives: to explore how individual commute to work in Kuala Lumpur by exploring modes of transportation used; to investigate the vehicle ownership and its impact on vehicle end-of-life. Data were collected from archive of Malaysian government report includes Malaysian Well-Being index and the Malaysian Transportation Statistics Report. Next, the research team visited residential areas, workshops and vehicle impound storage depots to collect data related to abandoned cars since they have an impact on the upward trend in car ownership and challenges in disposing those vehicles. The findings established that people commute extensively to work by car, causing traffic congestion in Kuala Lumpur. It was also found that there is no limitation on vehicle use, making public transportation the secondary choice to commute to work. Consequently, there is no policy related to car ownership and end-of-life vehicle in place which cause problems not only in increasing the use of vehicles but also on their disposal.